Personalized Services for Smart Grids in the framework of Society 5.0: A Smart University Campus Case Study - Mourtzis, Dimitris; Angelopoulos, John; Panopoulos, Nikos (Technical Annals, 2023)
The evolution of the power grid towards a Smart Grid is a crucial aspect of the transformation of society towards the so-called Society 5.0, where human-centered technology is the key to address social challenges. This paper proposes a personalized service approach for Smart Grids within the Society 5.0 framework, which aims to provide a personalized energy management service to consumers through advanced sensing technologies, intelligent algorithms, and social and contextual data. Furthermore, the paper highlights the potential of personalized services in the Smart Grid context and their relevance in the Society 5.0 framework and proposes an Architecture for the design and deployment of personalized energy management services in other Smart Grid contexts. In this approach end-users play an active role in the design and deployment of personalized energy management services. The proposed methodology is tested and evaluated in a Smart University Campus case study. The results indicate energy management improvement and energy consumption reduction.